2013
DOI: 10.1016/j.jbiomech.2013.07.043
|View full text |Cite
|
Sign up to set email alerts
|

Applied osmotic loading for promoting development of engineered cartilage

Abstract: This study investigated the potential use of static osmotic loading as a cartilage tissue engineering strategy for growing clinically relevant grafts from either synovium-derived stem cells (SDSCs) or chondrocytes. Bovine SDSCs and chondrocytes were individually encapsulated in 2% w/v agarose and divided into chondrogenic media of osmolarities 300 (hypotonic), 330 (isotonic), and 400 (hypertonic, physiologic) mOsM for up to 7 weeks. The application of hypertonic media to constructs comprised of SDSCs or chondr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…1b. Thus, the value of parameter β for bovine NP cells is 0.62, which is close to the value (~0.6) for mesenchymal stem cells (Sampat et al, 2013). …”
Section: Model Developmentsupporting
confidence: 71%
See 1 more Smart Citation
“…1b. Thus, the value of parameter β for bovine NP cells is 0.62, which is close to the value (~0.6) for mesenchymal stem cells (Sampat et al, 2013). …”
Section: Model Developmentsupporting
confidence: 71%
“…Osmotic loading and mechanical loading have been shown to affect the synthesis of GAG in vitro in both explant and cell culture experiments [e.g., (Bush and Hall, 2001; Gray et al, 1988; Gray et al, 1989; Guilak et al, 1994; Johnson et al, 2014; Maroudas and Evans, 1974; O'Conor et al, 2014; Sampat et al, 2013; Schneiderman et al, 1986; Urban et al, 1993)]. For example, the extracellular osmolarity has been found to have a dose-dependent effect on GAG synthesis rate by isolated cells (Ishihara et al, 1997; Negoro et al, 2008); the cells in the NP explant exhibit a higher synthesis rate of GAG at the osmolarity level close to the in situ value (van Dijk et al, 2011; van Dijk et al, 2013); the GAG synthesis rate has been observed to decrease in osmotic loaded articular cartilages (Bayliss et al, 1986; Schneiderman et al, 1986); a static compression has been shown to suppress GAG synthesis in articular cartilage (Kim et al, 1994; Schneiderman et al, 1986), whereas the GAG synthesis rate in bovine tail disc was found to be elevated if the static loading is less than 5 kg (Ohshima et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 4αPDD and hyperosmolarity interacted to enhance collagen content over hyperosmolarity alone (Figure 2). Previous studies have not examined the interaction of 4αPDD and hyperosmolarity on functional neocartilage properties, though they have investigated these agents independently (O'Conor et al, 2014; Sampat et al, 2013). Overall, the results of this study support 4αPDD as critical in affecting enhanced neocartilage properties, with 4αPDD able to augment the effects of other agents.…”
Section: Discussionmentioning
confidence: 99%
“…From these seminal studies, investigators have examined other types of physical stimuli such as combinations of different mechanical or physicochemical loading regimens that could even further improve construct qualities (Huang et al, 2012; Huey and Athanasiou, 2011; Jungreuthmayer et al, 2009; Meinel et al, 2004; Sampat et al, 2013; Schatti et al, 2011; Zhang et al, 2009). With further understanding of the role of the biomechanical microenvironment on cell behavior (Guilak et al, 2009; Reilly and Engler, 2010), other studies have examined the role of factors such as extracellular matrix topography or modulus within scaffolds as means of influencing local cellular responses (Dellatore et al, 2008; Gauvin et al, 2012; Guex et al, 2013; Kolambkar et al, 2014; Lim et al, 2011; Nii et al, 2013).…”
Section: Principles Of Functional Tissue Engineeringmentioning
confidence: 99%